2021
DOI: 10.1155/2021/5511010
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy: A Novel Horizon for Hair Cell Protection

Abstract: As a general sensory disorder, hearing loss was a major concern worldwide. Autophagy is a common cellular reaction to stress that degrades cytoplasmic waste through the lysosome pathway. Autophagy not only plays major roles in maintaining intracellular homeostasis but is also involved in the development and pathogenesis of many diseases. In the auditory system, several studies revealed the link between autophagy and hearing protection. In this review, we aimed to establish the correlation between autophagy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 148 publications
(170 reference statements)
0
6
0
Order By: Relevance
“…Interestingly, studies have shown that promoting lysosomal delivery through autophagy of aminoglycosides is cytoprotective [37]. Recently, autophagy has emerged as a potential target for treating various SNHL by decreasing oxidative stress levels and apoptosis [13,14]. In our experiments, the results show that MSC-derived exosomes can markedly activate autophagy both in the normal basal state and upon neomycin-induced damage conditions in hair cells.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Interestingly, studies have shown that promoting lysosomal delivery through autophagy of aminoglycosides is cytoprotective [37]. Recently, autophagy has emerged as a potential target for treating various SNHL by decreasing oxidative stress levels and apoptosis [13,14]. In our experiments, the results show that MSC-derived exosomes can markedly activate autophagy both in the normal basal state and upon neomycin-induced damage conditions in hair cells.…”
Section: Discussionmentioning
confidence: 54%
“…Autophagy has been demonstrated to be a core pathway for the preservation of cellular and organismal homeostasis, which is tightly involved in hair cell protection [13,14,25]. Therefore, we explored whether autophagy in hair cells could be enhanced by exosomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, research on the role played by autophagy in hearing loss is in an emergent phase (He et al, 2018;Ye et al, 2018;Fu and Chai, 2019;Guo et al, 2021;Liu C. et al, 2021). Certainly, more investigation into various auditory cells, including nonsensory cells, is needed to determine the autophagic function in specific cells involved hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, autophagy can remove damaged organelles, defend against microbial infection, and has a protective effect against metabolic, heart disease, and neurodegenerative diseases (including Parkinson's, Alzheimer's, and Huntington's) (Yu et al, 2004). In hair cells, autophagy plays an important role in preventing ototoxicity, including aminoglycoside-, cisplatin-, noise-, and age-induced hearing loss (Liu et al, 2021). Based on these findings, targeting autophagy to control mitochondrial quality appears to be a potential strategy to attenuate ototoxicity.…”
Section: Introductionmentioning
confidence: 99%